Book Review: Perbandingan Potret Diri Antar-Gereja, Tantangan dan Tanggapan - Nauval Hadhi Syahputra; Arisandie, Tio Pilus (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
This book contains the two-level struggle experienced by the churches during the Theological Consultation, the results of which were published by the PGI General Secretariat with the title 'Double Struggle'. There are six things that are the focus of the profile of 14 churches, namely (1) Church location and statistics, (2) Socio-cultural context, (3) Church history. (4) Organizational Structure, (5) Relations with other churches, (6) Relations between religions. Churches have experienced various challenges, such as financial challenges. Many churches in Indonesia in general were born as a result of mission work by churches from Europe and the United States. The financial and labor burden is borne by the parent church, namely the respective zending bodies. Churches also face challenges from external factors. There are several challenges to face. The final part of this book provides conclusions, namely several research findings and directions for change. The findings of this research are that the profiles of the churches studied have succeeded in revealing quite up-to-date data about the state of each church's service area and the latest statistical conditions, the socio-cultural context of each church, the history of church development, the organizational structure of each church, ecumenical relations between churches, and inter-religious relations.